The stratification of higher education in the USA and Taiwan: a comparative analysis of students' college-choice outcomes. Issue 5 (3rd September 2019) - Yu, Patricia
Abstract: This comparative study modifies Cabrera and La Nasa's model to examine social and class stratification in students' college-choice outcomes in the USA and Taiwan, and compares the mechanisms that perpetuate this stratification between the two systems. Students' college-choice outcomes are defined by both institutional selectivity and control, in order to test not only stratification in the quality of institution students attend but also their financial burden of college costs. The findings show that students from lower-socioeconomic backgrounds are less likely to attend high-selective institutions and institutions that embrace better resources and provide more subsidies to students. Current financing structures embedded in both systems increase stratification, but through different ways. In addition to enhancing academic preparation for socioeconomically disadvantaged students, fundamentally rethinking the financing structures – especially the distribution of public funds – is imperative to increase equality for both countries in the cost-sharing era.